2018
DOI: 10.1159/000491392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Liver Pathology and Disease Progression in a Murine Model of Amyotrophic Lateral Sclerosis

Abstract: Background: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that causes selective motor neuron cell death and accompanying skeletal muscle atrophy and structural deformities. In both patients with ALS and animal models, there appears to be spinal cord and muscle pathology. This pathology can be modeled in hSOD1G93A mice, which have a point mutation in the gene for superoxide dismutase 1. Similar to patients with ALS, hSOD1G93A mice present hepatic abnormalities and lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(42 reference statements)
3
11
0
Order By: Relevance
“…An earlier study found a high incidence of mild liver dysfunction in patients with ALS; ultrastructural changes of hepatocytes with intrahepatic metabolic abnormalities were consistently found in patients with ALS 32 . A more recent study demonstrated that inflammation and oxidative stress, as-well-as the up-regulation of hepatic fibrosisrelated proteins, induce liver dysfunction in transgenic ALS mice 33 . Thus, the present study provides evidence for a systemic pro-inflammatory innate immune response in the peripheral circulation of patients with ALS; this response is associated with increased disease burden and faster disease progression.…”
Section: Site Of Disease Onset Is Associated With Disease Progressionmentioning
confidence: 99%
“…An earlier study found a high incidence of mild liver dysfunction in patients with ALS; ultrastructural changes of hepatocytes with intrahepatic metabolic abnormalities were consistently found in patients with ALS 32 . A more recent study demonstrated that inflammation and oxidative stress, as-well-as the up-regulation of hepatic fibrosisrelated proteins, induce liver dysfunction in transgenic ALS mice 33 . Thus, the present study provides evidence for a systemic pro-inflammatory innate immune response in the peripheral circulation of patients with ALS; this response is associated with increased disease burden and faster disease progression.…”
Section: Site Of Disease Onset Is Associated With Disease Progressionmentioning
confidence: 99%
“…Furthermore, ALS patients display non-alcoholic fatty liver disease, without being overweight or obese, suggesting lipid homeostasis impairment (Dupuis et al, 2008;Nodera et al, 2015). Similar lipid disequilibrium phenotypes can be observed in transgenic mouse models of ALS (Lee and Yang, 2018) and Alzheimer's disease (Kim et al, 2016). Hepatic steatosis (fatty liver degeneration) seems to be a common phenotype associated with neurodegenerative disorders and neurodegeneration caused by viral infections (Gupta et al, 2012;Nash et al, 2016;Zolkipli et al, 2012).…”
Section: Discussionmentioning
confidence: 78%
“…A previous study has demonstrated that abnormal changes in the immune system owing to the elevation of peripheral NKT cell levels are associated with liver pathology and disease progression in hSOD1 G93A mice [ 11 ]. We also previously reported that the livers of hSOD1 G93A mice are associated with elevated inflammation, oxidative stress, and fibrosis-related protein expression following liver pathology and disease progression [ 13 ]. In this study, we found that the combined administration of BJIGT and RZ did not induce liver pathology, suggesting that this new therapeutic drug combination has the potential to effectively relieve inflammatory cytokines and cellular stress-related proteins in the liver of hSOD1 G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al showed liver dysfunction in patients with ALS [ 12 ]. In our previous study, we demonstrated that the levels of inflammation and oxidative-stress-related proteins are significantly increased with disease progression in hSOD1 G93A mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%